PENERAPAN METODE PEMBELAJARAN PQ4R BERBASIS LESSON STUDY TERHADAP SOFT SKILL MAHASISWA MATA KULIAH EKONOMI IPS TERPADU - Suprihatin, Siti (LPPM STKIP PGRI Bandar Lampung, 2019)
Application of the method is a regular method used to carry out a job in order to be achieved in accordance with what is desired. Method literally means a way in general use, the method is defined as a method or procedure used to achieve certain goals. Lesson Study as one of the models of the teaching profession development through collaborative and continuous learning assessment is based on the principles of collegiality and mutual learning to build learning communities. IPS is an embodiment of an interdisciplinary approach from social science. It is an integration of various branches of social sciences namely sociology, cultural anthropology, psychology, history, geography, economics, political science and human ecology, formulated for instructional purposes with simplified material and goals for easy learning. Soft skills are very important given to learning process. So graduates produced can become graduates who are ready to use in the world of work that not only have hard skills but also soft skills. Some soft skills, among others; communication, honesty, cooperation, interpersonal, work ethic, discipline, motivation, adaptation, organization, confidence, ethics, wise, creative, humorous, entrepreneurship. This article aims to: to determine the effect of the Lesson Study-based PQ4R (Preview Question Read Reflect Recite Review) method on the soft skills of students of integrated social economics courses at the University of Muhammadiyah Metro Academic Year 2017/2018